LIFETIME INBREEDING DEPRESSION, PURGING, AND MATING SYSTEM EVOLUTION IN A SIMULTANEOUS HERMAPHRODITE TAPEWORM. (28th March 2014) - Benesh, Daniel P.; Weinreich, Friederike; Kalbe, Martin; Milinski, Manfred
<x xml:space="preserve">Abstract</x> Classical theory on mating system evolution suggests that simultaneous hermaphrodites should either outcross if they have high inbreeding depression (ID) or self‐fertilize if they have low ID. However, a mixture of selfing and outcrossing persists in many species. Previous studies with the tapeworm Schistocephalus solidus have found worms to self‐fertilize some of their eggs despite ID. The probability for selfing to spread depends on the relative fitness of selfers, as well as the genetic basis for ID and whether it can be effectively purged. We bred S. solidus through two consecutive generations of selfing and recorded several fitness correlates over the whole life cycle. After one round of selfing, ID was pronounced, particularly in early‐life traits, and the conservatively estimated lifetime fitness of selfed progeny was only 9% that of the outcrossed controls. After a second generation of selfing, ID remained high but was significantly reduced in several traits, which is consistent with the purging of deleterious recessive alleles (the estimated load of lethal equivalents dropped by 48%). Severe ID, even if it can be rapidly purged, likely prevents transitions toward pure selfing in this parasite, although we also cannot exclude the possibility that low‐level selfing has undetected benefits.